Influence of female sex and fertile age on neuromyelitis optica spectrum disorders - Borisow, Nadja; Kleiter, Ingo; Gahlen, Anna; Fischer, Katrin; Wernecke, Klaus-Dieter; Pache, Florence; Ruprecht, Klemens; Havla, Joachim; Krumbholz, Markus; Kuempfel, Tania; Aktas, Orhan; Ringelstein, Marius; et al. (Multiple sclerosis journal, 2017)
Gender and age at onset are important epidemiological factors influencing prevalence, clinical presentation, and treatment response in autoimmune diseases.To evaluate the impact of female sex and fertile age on aquaporin-4-antibody (AQP4-ab) status, attack localization, and response to attack treatment in patients with neuromyelitis optica (NMO) and its spectrum disorders (neuromyelitis optica spectrum disorder (NMOSD)).Female-to-male ratios, diagnosis at last visit (NMO vs NMOSD), attack localization, attack treatment, and outcome were compared according to sex and age at disease or attack onset.A total of 186 NMO/SD patients (82% female) were included. In AQP4-ab-positive patients, female predominance was most pronounced during fertile age (female-to-male ratio 23:1). Female patients were more likely to be positive for AQP4-abs (92% vs 55%; p < 0.001). Interval between onset and diagnosis of NMO/SD was longer in women than in men (mean 54 vs 27 months; p = 0.023). In women, attacks occurring ?40 years of age were more likely to show complete remission ( p = 0.003) and better response to high-dose intravenous steroids ( p = 0.005) compared to woman at >40 years.Our data suggest an influence of sex and age on susceptibility to AQP4-ab-positive NMO/SD. Genetic and hormonal factors might contribute to pathophysiology of NMO/SD.
EVALuna2:22502